Inhibition of Lung Tumor Development in ApoE Knockout Mice via Enhancement of TREM-1 Dependent NK Cell Cytotoxicity - Lee, Yong Sun; Yeo, In Jun; Kim, Ki Cheon; Han, Sang-Bae; Hong, Jin Tae (Frontiers in Immunology, 2019)
Apolipoprotein E (ApoE) is known to regulate lipid homeostasis and associated with atherosclerogenesis. Eventhough atherosclerogenesis is associated with tumor development, the role of ApoE in lung tumorigenesis and metastasis is not clear. Thus, the tumor growth and metastasis were compared in WT and ApoE knockout (KO) mice. Urethane-induced lung tumor incidence and B16F10 lung metastasis in ApoE knockout (KO) mice were significantly reduced in comparison to that in WT mice. Knockdown of ApoE expression in lung cancer cells and B16F10 cells also decreased cancer cell growth and metastasis. The inhibitory effect of ApoE KO on tumor development and metastasis was associated with increase of infiltration of NK cells. NK cells derived from ApoE KO mice showed much greater cytotoxicity than those from WT mice. These cytotoxic effect of NK cells derived from ApoE KO mice was associated with higher expression of Granzyme B, Fas Ligand, IFN-γ, TNF-α, NKG2D, NKp46 and DNAM-1 expression. Triggering receptor expressed on myeloid cell (TREM)-1 is a proinflammatory mediator expressed on NK cells, and is known to be associated with NK cell cytotoxicity. Thus, we investigated the role of TREM-1 on ApoE KO mice originated NK cell mediated cytotoxicity for cancer cells. Blockade of TREM-1 expression with a TREM-1 antagonist prevented NK cell-mediated cytotoxicity. TREM-1 antibody recovered cytotoxic effect of NK cells derived from KO mice of T-bet, which upregulating gene for TREM-1. These data indicate that ApoE KO suppressed lung tumor development and metastasis via increase of TREM-1-dependent anti-tumor activity of NK cells.